Notes on Bhutan’s Gross National Happiness and its Measurement - Monaco, Eduardo (Journal of Management and Development Studies, 2016)
Bhutan, a Himalayan landlocked country of just about 750,000 inhabitants, has since the 1980s adopted a unique, holistic approach to development governance commonly referred to as ’Gross National Happiness’ (GNH), which aims at achieving equitable socio-economic progress in harmony with other fundamental ’pillars’ such as environmental preservation, good governance, and protection of the local cultural identity. The strategy - inspired, above all, by solid Tantric Buddhist belief - significantly differentiates itself from the mainstream GDP-driven, output-maximizing paradigms by maintaining that truly sustainable development can only originate from acknowledging the equal dignity and crucial interdependence of various dimensions of both human and natural life. This paper, drafted in the month of December 2015, briefly analyzes GNH policy’s key tenets and achievements – more conspicuous in regards to democratic governance and environment than in terms of inclusive, multidimensional poverty reduction, as well as its recently devised measuring tool, the GNH Index, and the results of its latest surveys. Factors like the peculiar Buddhist culture that informs it, the relatively simple economic infrastructure at this early stage of development, as well as the limited size of the politically active, urbanized population, all make GNH per se a distinctively Bhutanese phenomenon. Nevertheless, the fundamental paradigm shift that GNH advocates has already resonated beyond the countries’ borders, reinforcing a growing trend across international development actors towards a more comprehensive, qualitative definition and measurement of societal development.